Development of the Multi-Dimensional Analysis of Patient Outcome Predictions (MD.POP) during medical encounters. Issue 1 (January 2018) - Ménard, Catherine; Libert, Yves; Canivet, Delphine; Van Achte, Laetitia; Farvacques, Christine; Liénard, Aurore; Merckaert, Isabelle; Reynaert, Christine; Slachmuylder, Jean-Louis; Durieux, Jean-François; Klastersky, Jean; Razavi, Darius
Highlights: MD.POP is an interaction analysis system. MD. POP assesses how HCPs discuss patient outcomes during medical encounters. Patient outcomes refer to any medical, psychological or social outcomes. MD.POP shows excellent interrater reliability. Abstract: Objective: Our first objective was to develop the Multi-Dimensional analysis of Patient Outcome Predictions (MD.POP), an interaction analysis system that assesses how HCPs discuss precisely and exclusively patient outcomes during medical encounters. The second objective was to study its interrater reliability. Method: The MD.POP was developed by consensus meetings. Forty simulated medical encounters between physicians and an actress portraying a patient were analysed. Interrater reliability analysis was conducted on 20 of those simulated encounters. Results: The MD.POP includes six dimensions: object, framing, value, domain, probability and form of POP. The coding method includes four steps: 1) transcription of the encounter, 2) POP identification, 3) POP dimension coding and 4) POP scoring. Descriptive analyses show that the MD.POP is able to describe verbal expressions addressing the patient's outcomes. Statistical analyses show excellent interrater reliability (Cohen's Kappa ranging from 0.92 to 0.94). Conclusion: The MD.POP is a reliable interaction analysis system that assesses how HCPs discuss patient medical, psychological or social outcomes during medical encounters. Practical implication: The MD.POP provides a measure for researchers to study how HCPs communicate with patients about potential outcomes. Results of such studies will allow to provide recommendations to improve HCP's communication about patients' outcomes.